34.3: Invited Paper: Printing Pixel Circuits on Light Emitting Diode Array for AMLED Displays. (4th October 2019) - Li, Huaping
Abstract : An active matrix light emitting display module integrated with carbon nanotubes control circuits was fully printed. The high performance of super pure single‐chirality carbon nanotube TFT provides super bright and low power consumption technologies for indoor and outdoor augmented reality that are highly desirable for civil and military display applications.